Reflections on biochemistry : in honour of Severo Ochoa - Ochoa, Severo, 1905-1993; Kornberg, Arthur, 1918-2007 (Pergamon Press, 1976)
Reflections on Biochemistry: In Honour of Severo Ochoa offers reflections on a wide range of topics relating to biochemistry, including energy metabolism, lipids and saccharides, regulation, nucleic acids and the genetic code, protein biosynthesis, and cell biology. The essays celebrate Severo Ochoa's outstanding contributions to biochemistry spanning nearly half a century.